Talkshow Program Production Analysis "Sapa Pagi" on Madu TV Nusantara Tulungagung: Indonesia - Jannah, Miftakhul; Faristiana, Andhita Risko (Jurnal Ilmu Komunikasi, 2023)
The existence of local television has a position in conveying various local wisdoms in channeling local information and preserving local culture that has not been touched by private and national television media. The Sapa Pagi program is a light information program that presents the latest hot issues and inspirational broadcasts obtained from the local and national regions. This study uses a descriptive qualitative approach. The results of the study explain that the production process carried out in the Sapa Pagi program on Madu TV Nusantara is in accordance with the work standard that applies to television media. The pre-production stage includes the formation of the production team, meeting, determining the theme of discussion, determining and searching for sources, gathering discussion material, preparing presenters, promotions, and preparing equipment. The production phase focuses on shooting and using Zoom Meeting as a live virtual production mediator. While the post-production stage emphasizes archiving and evaluation, seeing the movement of ratings and shares as the final stage of the entire production.